ELEMENTAL ANALYSIS OF LOCAL AND FOREIGN RAW MATERIALS FOR THE PRODUCTION OF TRIMANGANESE TETRAOXIDE PIGMENT - R. Z. Safarov,; A. Zhandildenova,; D. B. Kargin,; B. B. Makhmutov,; R. M. Kamatov,; Zh. K. Shomanova, (Academic Scientific Journal of Chemistry, 2021)
In the course of continuation of scientific research in the development of Kazakhstani technology for the production of trimanganese tetraoxide pigment, there have been proposed new methods of analysis which make it possible to investigate new nanostructural materials sourced from local deposits. The results obtained are of practical importance and serve as the foundation for developing new technologically advanced domestic production of a competitive product that is in demand both on the national and international markets. The available methods are not able to highlight the particularity and diversity of Kazakhstani manganese ores due to the uneven distribution of manganese minerals and host (waste) rock, the quantitative ratio of rock-forming components and their variation instability. Methods of energy-dispersive analysis of manganese ores from Kazakhstani Zhaksylyk and Bogach deposits have been put forward, electronic micrographs, spectrograms of samples, diagrams of normalized distribution of elements on the surface of samples have been obtained and a comparative analysis with raw analogue samples of some foreign manufacturers has been performed